2008
DOI: 10.1111/j.1365-313x.2008.03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient virus‐induced gene silencing in Arabidopsis using a ‘one‐step’ TYMV‐derived vector

Abstract: ). † These authors contributed equally to this work. SummaryVirus-induced gene silencing (VIGS) is an important tool for the analysis of gene function in plants. This technique exploits recombinant viral vectors harbouring fragments of plant genes in their genome to generate double-stranded RNAs that initiate homology-dependent silencing of the target gene. Several viral VIGS vectors have already been successfully used in reverse-genetics studies of a variety of processes occurring in plants. Here, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 72 publications
1
76
0
3
Order By: Relevance
“…These results are consistent with those using ALSV in soybean, where the 5# end PDS sense insertion had little PDSsilencing effect (Igarashi et al, 2009). Similar results were also reported in Arabidopsis, where sense insertion in TYMV had minimal effect on GUS transgene and PDS silencing (Pflieger et al, 2008). Here, we found that the antisense orientation generally resulted in stronger silencing phenotypes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These results are consistent with those using ALSV in soybean, where the 5# end PDS sense insertion had little PDSsilencing effect (Igarashi et al, 2009). Similar results were also reported in Arabidopsis, where sense insertion in TYMV had minimal effect on GUS transgene and PDS silencing (Pflieger et al, 2008). Here, we found that the antisense orientation generally resulted in stronger silencing phenotypes.…”
Section: Discussionsupporting
confidence: 78%
“…This difference is likely due to the fact that pBPMV-GFP-BAR is larger than pBPMV-GFP2; thus, we do not expect the double gene expression construct to replicate and move as efficiently and quickly as the smaller single gene expression construct. While the biolistic inoculation is highly efficient, inoculation by direct DNA rubbing may make use of the BPMV vectors even more facile, as was reported for Soybean mosaic virus (SMV; Seo et al, 2009) in soybean and Turnip yellow mosaic virus (TYMV; Pflieger et al, 2008) in Arabidopsis (Arabidopsis thaliana). We evaluated direct DNA rubbing of soybean seedlings for two constructs: pBPMV-P19, which expresses the heterologous TBSV P19 RNA-silencing suppressor; and the RNA-silencing construct pBPMV-PDS-3R, which contains an endogenous PDS gene 3# ORF antisense insertion in the BPMV RNA2.…”
Section: Gene Expression In Shoots and Roots Of P Vulgarismentioning
confidence: 99%
“…Expression of a hairpin-loop dsRNA structure generated a stronger silencing than expression of the corresponding sense or anti-sense cDNA (Waterhouse et al, 1998;Smith et al, 2000;De Buck et al, 2001). It has been reported that insertion of direct inverted-repeat sequences of target genes that could fold as dsRNA hairpin structures strongly enhance VIGS from Tobacco mosaic virus, BSMV (Lacomme et al, 2003), and Turnip yellow mosaic virus (Pflieger et al, 2008). This is true for pFoMV-sgmediated VIGS.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to the insert size and position of target genes, the effect of the cloning orientation of the foreign gene was investigated using white lupin plants. No clear differences were detected between sense and antisense orientations in this study (Figure 4), although antisense fragments have been shown to be more effective for silencing in other VIGS systems (Igarashi et al 2009;Pflieger et al 2008;Zhang et al 2010). …”
Section: Discussionmentioning
confidence: 60%